DESIGN OF AUTHOR COUTURE COLLECTION IN ECO-STYLE WITH THE USE OF PRINTING TECHNIQUE - Краснюк, Л. В.; Матрофайло, М. В.; Троян, О. М. (Art and Design, 2018)
The development and production of the author couture collection using the printing technique based on the analysis and application of the main eco-style features as well as on the research of the physical and mechanical properties of natural materials with linen fibers. The basic principles of the systematic approach to design development of the author collection, such as literary-analytical research, morphological analysis, figurative and associative stylization of the source of creativity, were used in the process. The properties of materials were researched by means of standard techniques.